ANALISI KEBUTUHAN PENGGUNA SISTEM INFORMASI SURVEI STATUS GIZI INDONESIA (SSGI) MENGGUNAKAN METODE USER EXPERIENCE - Kurniadi, Willy; Latifah, Fitri (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2024)
Stunting is the most common form of malnutrition in children under five years of age and this condition can be an indicator of chronic nutritional status which can provide an overview of economic disruption and family food security. Stunting in toddlers in developing countries can be caused by many factors. In overcoming and suppressing stunting cases, the Indonesian government through health metrics uses the Indonesian Toddler Nutrition Status Survey (SSGI) application. This research was carried out to ensure whether the SSGI application met the standards expected by users. This research uses the user experience method. The results obtained in this research are that there is a tutorial or guide that helps users understand how to use the application, there needs to be a Standard Operating Procedure (SOP) for application users, there is a need for collaboration with internet services to optimize internet performance for the application.